2002
DOI: 10.1063/1.1524392
|View full text |Cite
|
Sign up to set email alerts
|

Optical System Design for High-Energy Particle Beam Diagnostics

Abstract: Abstract. Radiation generated by high-energy particle beams is widely used to characterize the beam properties. While the wavelengths of radiation may vary from visible to x-rays, the physics underlying the engineering designs are similar. In this tutorial, we discuss the basic considerations for the optical system design in the context of beam instrumentation and the constraints applied by high-radiation environments. We cover commonly used optical diagnostics: fluorescence flags, visible and x-ray synchrotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…[Camera Pixel Size] Numerical simulation showed that the finite size of the camera sensor pixel makes the following contribution to the rms resolution [7]:…”
Section: Absolute Photon Flux and Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…[Camera Pixel Size] Numerical simulation showed that the finite size of the camera sensor pixel makes the following contribution to the rms resolution [7]:…”
Section: Absolute Photon Flux and Efficiencymentioning
confidence: 99%
“…Integration of the intensity over ycoordinates resulted in a double-peaked profile of x-coordinates (Figure 3.11B). Fitting the profile to Gaussian functions [7,15] Hence we can use an average value of 5 µm as the diffraction-limited resolution over the entire visible region.…”
Section: Estimate Diffraction-limited Resolutionmentioning
confidence: 99%
“…A general discussion of beam diagnostics with synchrotron light is covered in Refs. [1][2][3][4][5], while a few site-specific examples are included in Refs. [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…There are OSR ports on both the AR and IS, and there are both an OSR port and an x-ray synchrotron radiation (XSR) port on the storage ring. The SR OSR is typically used for bunchlength measurements with a streak camera while the XSR is used with a pinhole camera to provide ~ 22 µm (σ) resolution beam size imaging [6].…”
Section: Experimental Backgroundmentioning
confidence: 99%